Dirty god - Reinders, Rutger ca. 20. Jh (Modern Films, 2019)
"The film follows single mother Jade (Vicky Knight) in the aftermath of an acid attack as she tries to come to terms with facial disfigurement and readjust to normal life. After being attacked by her ex-boyfriend, Jade undergoes surgery and rehabilitation sessions before the perpetrator is put on trial. But as she tries to quell her rage and find love and happiness again, will she ever find a way to feel comfortable in her own skin? Knight makes an electrifying screen debut in this sensitive exploration of the challenges of living with a visible difference." [shop.bfi.org.uk]
Original: Niederlande, Großbritannien, Belgien, Irland 2019
bonus feature: "Being different is okay"
Bildformat 2.35:1
Keywords: Film; DVD-Video